Paradoks Gender dalam Visualisasi Gotong Royong: Analisis Kritis Buku Teks Pendidikan Pancasila Sekolah Dasar - Kemil Wachidah; Vanda Rezania (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
Textbooks function not only as learning resources but also as powerful instruments for transmitting social values and gender ideology to students from an early age. This study aims to critically examine gender bias in the visualization of social roles and the concept of Gotong Royong (mutual cooperation) as presented in elementary school textbooks. Employing a critical content analysis approach, the research analyzes visual representations found in Pancasila Education and Social Sciences textbooks used at the elementary level. The findings reveal a significant gender paradox embedded within textbook illustrations. Although Gotong Royong is promoted as a collective and inclusive cultural value, its visual portrayal tends to emphasize masculine leadership and dominance in public roles. Male figures are repeatedly depicted occupying strategic and authoritative positions such as flag bearers, police officers, doctors, and community leaders. In contrast, female figures are predominantly represented in domestic, supportive, or subordinate roles. This visual segregation contributes to the formation of a hidden curriculum that subtly reinforces gender inequality, restricts female students’ aspirations in the public sphere, and normalizes the stigma of women’s “double burden.” Therefore, this study underscores the urgency of reconstructing visual representations in independent curriculum textbooks to promote gender equality and foster inclusive educational values